2016
DOI: 10.3390/rs8060493
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Qinghai-Xizang Plateau Monsoon Evolution and Its Linkages with Soil Moisture

Abstract: Abstract:The evolution of plateau monsoons is essential to synoptic climatology processes over the Qinghai-Xizang Plateau. Based on ERA-Interim Reanalysis data covering 1979-2014 from the European Centre for Medium-Range Weather Forecasts (ECMWF), we propose a new plateau monsoon index (ZPMI) that can effectively reflect the evolution of monsoons and compare this new index with the existing Plateau Monsoon Indices (PMI), i.e., the Traditional Plateau Monsoon Index (TPMI), the Dynamic Plateau Monsoon Index (DPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the timescale of the soil moisture observation data used in the study as of now is approximately 10 years. Consequently, for regional‐scale or long‐term climate research, model‐derived soil moisture data are often utilized as an alternative (Zuo and Zhang, ; Zhou et al ., ). Previous evaluations of several reanalysis data sets showed that the ERA‐40 reanalysis could generally capture the inter‐annual variations of soil moisture from the surface to deeper layers over China (Li et al ., ; Zhang et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the timescale of the soil moisture observation data used in the study as of now is approximately 10 years. Consequently, for regional‐scale or long‐term climate research, model‐derived soil moisture data are often utilized as an alternative (Zuo and Zhang, ; Zhou et al ., ). Previous evaluations of several reanalysis data sets showed that the ERA‐40 reanalysis could generally capture the inter‐annual variations of soil moisture from the surface to deeper layers over China (Li et al ., ; Zhang et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…With respect to the reliability of the reanalysis data, some scholars (Qi et al, 2009; Hua et al ., ; Zhou et al ., ) have used ECMWF reanalysis data to calculate plateau monsoon indices. Therefore, it is feasible to utilize ERA‐Interim data for the study of plateau monsoons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [30] explored the linkage between soil moisture and the Qinghai-Xizang Plateau monsoon evolution, and proposed a new plateau monsoon index (ZPMI). The ZPMI was compared with the existing Plateau Monsoon Indices (PMI): the Traditional Plateau Monsoon Index (TPMI), the Dynamic Plateau Monsoon Index (DPMI), and the QPMI (i.e., PMI developed by Qi et al).…”
Section: Water Cycle and Climate From Spacementioning
confidence: 99%
“…It is produced by a data assimilation system based on a 2006 release of the ECMWF Integrated Forecasting System. As discussed in [32][33][34], the Tiled ECMWF Scheme for Surface Exchanges over Land (TESSEL) land-surface model is used for the ERA-Interim model. Specifically, the ERA-Interim model uses the TESSEL [35,36] scheme to evolve the thermal and water storage in the four layers of soil and snow during the forecast.…”
Section: Ecmwf Datamentioning
confidence: 99%